The EGEE European Grid Infrastructure Project - Gagliardi, Fabrizio (High Performance Computing for Computational Science - VECPAR 2004, 2005)
The state of computer and networking technology today makes the seamless sharing of computing resources on an international or even global scale conceivable. Extensive computing Grids that integrate large, geographically distributed computer clusters and data storage facilities have changed from representing a dream to becoming a vision and, with the Enabling Grids for E-science in Europe project (EGEE), a reality today. EGEE aims to provide a European Grid infrastructure for the support of many application domains. This infrastructure is built on the EU Research Network GEANT and exploits Grid expertise that has been generated by previous projects. EGEE is a EU funded project that involves 71 partners from Europe, Russia and the United States. The project started in April 2004 for a first phase of 2 years.